2017
DOI: 10.1097/txd.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

5 Years Experience With Drug Eluting and Bare Metal Stents as Primary Intervention in Transplant Renal Artery Stenosis

Abstract: BackgroundTransplant renal artery stenosis (TRAS) is a common vascular complication after kidney transplantation and is associated with refractory hypertension, volume overload, and graft injury or loss. This article describes 5-year outcomes of endovascular intervention for TRAS with bare metal and drug eluting stents (DES).MethodsWe investigated, as a prospective cohort study, patient and graft outcomes after the targeted use of DES for vessel diameter less than 5 mm and bare metal stents (BMS) for vessel di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Regarding the functional outcomes after endovascular intervention, our study failed to show a statistically significant improvement in graft renal function after the procedure, as described by previous series [ 17 , 20 , 21 ]. This finding might have different explanations.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Regarding the functional outcomes after endovascular intervention, our study failed to show a statistically significant improvement in graft renal function after the procedure, as described by previous series [ 17 , 20 , 21 ]. This finding might have different explanations.…”
Section: Resultssupporting
confidence: 65%
“…Both the DU criteria for suspicion of TRAS and the specific RCs and PSs used in our protocol were adapted from available definitions in the literature and defined according to our personal experience. However, as shown in a recent systematic review of the literature, there is wide heterogeneity regarding the definitions of TRAS diagnostic criteria, the triggers for interventions, the reporting of treatment outcomes, and types of follow-up schedules [ 4 , 21 , 22 ]. As such, we designed a follow-up protocol that could capture the different risk of TRAS in the single KT patient and adjust the intensity and invasiveness of treatment accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Transplant renal artery stenosis (TRAS), which is evidenced by refractory hypertension and graft dysfunction, has become an increasingly recognized cause of poor long-term patient and allograft survival [ 1 ]. It is reported that the incidence of TRAS ranges from 6% to 23%, depending on the diagnostic criteria, which shows wide variability among reports [ 2 ]. The commonly accepted definition of hemodynamically significant TRAS is arterial lumen stenosis greater than 50% and/or a peak systolic velocity (PSV) exceeding 200 cm/s as measured by ultrasound, computed tomography angiography (CTA), and digital subtraction angiography (DSA) [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A greater than 50% narrowing in the renal artery intraluminal diameter or a greater than 15 mmHg pressure drop crossing the stenotic segment is considered to be TRAS . The color Doppler ultrasonography (CDU) standard for the diagnosis of TRAS is peak systolic velocity (PSV) of >2 m/s or a prestenotic segment flow velocity to poststenotic–prestenotic segment ratio of >2:1 …”
Section: Introductionmentioning
confidence: 99%
“…15 The color Doppler ultrasonography (CDU) standard for the diagnosis of TRAS is peak systolic velocity (PSV) of >2 m/s or a prestenotic segment flow velocity to poststenotic-prestenotic segment ratio of >2:1. 16,17 There are several causes for TRAS, some of which are controversial. Stenosis of anastomotic stoma might be caused by trauma to the donor or recipient vessels during kidney harvesting and transplantation.…”
mentioning
confidence: 99%